Mechanism of Energy Conversion in ATP Driven Molecular Machines: Development of Single-molecule Techniques for Observation of Conformational Changes in Sec Translocon during Protein Transport - Sulejmani, Edrin (Jihočeská univerzita, 2023)
Optimization and application of single-molecule techniques, respectively smFRET ALEX confocal microscopy with epi-fluorescence configuration, for examination of conformational space of the SecA in simulated biological conditions.
Mechanism of Energy Conversion in ATP Driven Molecular Machines: Development of Single-molecule Techniques for Observation of Conformational Changes in Sec Translocon during Protein Transport
Mekanizmi i konvertimit energjetik ne makinerite molekulare te asistuara nga ATP: Zhvillimi i teknikave nje-molekulare per observim te ndryshimeve konfiguracionale ne Sec Translokon pergjate transportimit proteinik
Keywords: SecA; SecYEG complex; configuration; 'open' conformation; 'closed' conformation; FRET; ATP; PPXD; HWD; NBD2; SecA; SecYEG complex; configuration; 'open' conformation; 'closed' conformation; FRET; ATP; PPXD; HWD; NBD2